CONSTRUCTION OF POLITICAL COMMUNICATION BY AGENTS OF COLOR REVOLUTIONS: EVERSION AND MOBBER TECHNOLOGIES - A. S. Konstantinova; M. M. Abazalieva (Современная наука и инновации)
A significant goal of political communication is to attract the attention of the Respondent, persuasion and stimulation to action. Therefore, the information impact of the subject on the object of communication pursues the goals set by the subject. The goals pursued by political strategists interested in" exporting revolutions " are achieved by interfering in the political communication processes of a number of countries. Given the pace of development of modern information and communication processes, the all-inclusive level of mobile operators in different countries, etc., it is safe to assume that information and communication processes focused on the governments of different countries will have an active continuation.